PEMANFAATAN APLIKASI ANDROID DAN VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DALAM MATERI JARINGAN KOMPUTER - Arif Sulistyo Atmoko (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2020)
The purpose of this activity is to improve the learning outcomes of students in studying computer network material using teaching media in the form of an Android application to replace MMS and learning videos. The subjects of this activity were students of class XII IPA 4 SMA N 1 PECANGAAN. The method used in this activity is syncronous and asyncronous.In carrying out this activity, students are asked to take the pre-test and post-test. The result of this activity was an increase in the knowledge and understanding of students about computer network material